The Influence of Self-Compassion and Psychological Flexibility on Psychological Distress in Early Adults Who Work - Amara, Keisha Putri; Sovitriana, Rilla (Dinasti Health and Pharmacy Science, 2024)
This study aims to determine whether there is an effect of self-compassion and psychological flexibility on psychological distress in early adults who work in DKI Jakarta. Researchers used quantitative methods. The sampling technique in this study used purposive sampling by distributing questionnaires to 130 subjects who work in DKI Jakarta and are 20- 39 years old. The instruments that researchers used in this study were the Self-Compassion Scale (SCS), Acceptance and Action Questionnaire - II (AAQ-II), and The Kessler Psychological Distress Scale 10 (K 10). Hypothesis testing through multiple linear regression. Based on the results of research on self-compassion variables obtained p value = 0.001 (p < 0.005) with a value of R2 = 19%, meaning that Ha1 is accepted, namely there is a negative influence between self-compassion and psychological distress. In the psychological flexibility variable, the value of p = 0.001 (p < 0.005) is obtained with a value of R2 = 35%, meaning that Ha2 is accepted, namely there is a negative influence between psychological flexibility and psychological distress. The results of multiple linear regression show that self-compassion and psychological flexibility have an influence on psychological distress.